Proceedings of the 21st European Conference on Pattern Languages of Programs 2016
DOI: 10.1145/3011784.3011812
|View full text |Cite
|
Sign up to set email alerts
|

From requirement to design patterns for ubiquitous computing applications

Abstract: Ubiquitous Computing describes a concept where computing appears around us at any time and any location. Respective systems rely on context-sensitivity and adaptability. This means that they constantly collect data of the user and his context to adapt its functionalities to certain situations. Hence, the development of Ubiquitous Computing systems is not only a technical issue and must be considered from a privacy, legal and usability perspective, too. This indicates a need for several experts from different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 16 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, it should not be neglected that, in addition to DPs, other forms of presentation can be used to record design knowledge. Thus, design knowledge can also appear in patterns or requirements (e.g., [28]). Nevertheless, within the DSR community, it is widely shared that DPs are seen as the right way to formalize DSR efforts and abstract the research findings to allow knowledge accumulation within the community [29].…”
Section: Dps As Generalizable Design Knowledgementioning
confidence: 99%
“…Nevertheless, it should not be neglected that, in addition to DPs, other forms of presentation can be used to record design knowledge. Thus, design knowledge can also appear in patterns or requirements (e.g., [28]). Nevertheless, within the DSR community, it is widely shared that DPs are seen as the right way to formalize DSR efforts and abstract the research findings to allow knowledge accumulation within the community [29].…”
Section: Dps As Generalizable Design Knowledgementioning
confidence: 99%
“…We describe the process of data extraction of the 10 studies remaining in Section 3. These studies are identified throughout this paper as S1 to S10 as follows: S1 -Adaptive requirement-driven architecture for integrated healthcare systems (Yang et al, 2010) S2 -Analysing security requirements patterns based on problems decomposition and composition (Wen et al, 2011) S3 -An architectural framework of the integrated transportation information service system (Chang and Gan, 2009) S4 -Application of ontologies in identifying requirements patterns in use cases (Couto et al, 2014) S5 -Effective security impact analysis with patterns for software enhancement (Okubo et al, 2011) S6 -From requirement to design patterns for ubiquitous computing applications (Knote et al, 2016) S7 -Modeling design patterns with description logics: A case study (Asnar et al, 2011) S8 -Mutation patterns for temporal requirements of reactive systems (Trakhtenbrot, 2017) S9 -SACS: A pattern language for Safe Adaptive Control Software (Hauge and Stølen, 2011) S10 -Re-engineering legacy Web applications into RIAs by aligning modernization requirements, patterns and RIA features (Conejero et al, 2013) . A detailed view of the conduction phase: automatic search, duplicate study exclusion, study selection, data extraction, snowballing, and data synthesis.…”
Section: Selection Of Primary Studiesmentioning
confidence: 99%